Liturgi Sebagai Ruang Transformasi: Sebuah Tawaran Misional untuk Pembaruan Liturgi - Hizkia Anugrah Gunawan (Indonesian Journal of Theology, 2018)
Echoes of liturgical renewal have come to pervade a number of churches these past decades. Alternatively, one finds that the discourse concerning mission is being abandoned by the church and domain of theology, alike. Yet a closer look at the principles undergirding the liturgical renewal movement shows a certain connection between liturgy and mission. Notion of a missional liturgy further emphasizes the link between the two. Constructive efforts leading to these findings thus generate enthusiasm for the renewal of liturgy as transformative space. This enthusiastic spirit ought to encourage the church to designate liturgy as space within which the church is to perform its mission.